(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides a comprehensive analysis of the theoretical and legal foundations of personal data terminology. The study examines the content and correlation of key concepts such as “personal data,” “privacy,” “identification,” as well as the subjects involved in data processing. A comparative analysis of international legal experience, particularly the European Unionʼs GDPR framework, and national legislation is conducted, identifying existing differences in terminological approaches and their practical implications. The research substantiates the necessity of systematizing personal data terminology, clarifying it on the basis of a unified scientific and legal approach, and adapting it to the requirements of the modern digital environment.